Parental Knowledge, Attitude, and Practice on Tobacco Use, Smoking Cessation, and Children's Environmental Tobacco Smoke Exposure - Dai, Siyu; Au, Chun Ting; Chan, Michael Ho Ming; Kam, Richard Kin Ting; Li, Albert Martin; Chan, Kate Ching-Ching (Frontiers in Public Health, 2021)
Background: Environmental tobacco smoke (ETS) exposure in children ranks one of the major public health problems in our time. Poor parental knowledge, attitude and practice (KAP) on ETS often contribute to worse exposure of the kids. Thus, we aimed to document parental KAP regarding tobacco use, smoking cessation and children’s ETS exposure, and to analyse how knowledge and attitude relate to practice. Methods: Self-administered KAP questionnaires were distributed to smoking parents recruited from the pediatric unit at the Prince of Wales Hospital, which provides pediatric service to a population of 1.2 million in Hong Kong. The 60-item questionnaire had a range of 0–38 for knowledge, 0–44 for attitude and 0–40 for practice. Descriptive analyses were performed for KAP response, chi-square and regression analyses were performed for the exploration of associations and identification of predictive indicators. Results: 145 smoking parents (mean age: 38.0 ± 6.7 yrs.; male: 85.5%) were included. Less than half (39.3%) of them reported a “smoke-free policy” at home. Among those parents who had private cars, less than half (45.2%) of them had “smoke-free policy” in their car. Only 25.5% of the participants correctly answered ≥70% of the knowledge questions, and 11.8 % of the participants gave favourable responses to ≥70% of the attitude questions. The total knowledge and the total attitudes score were positively associated (r=0.49, 95% CI: 0.35-0.79, p<0.001), yet they were only modestly correlated with parental practice on children’s ETS. According to the multivariate regression analyses, potential predictive factors for more favourable parental KAP included: higher parental education level, higher household income, lower parental nicotine dependence level and breastfeeding practice. Conclusions: Parental KAP related to tobacco use and children’s ETS exposure needs improvement to address the significant gap between recommended and actual practice. The weak correlation between knowledge and practice suggested that parental education alone is not adequate to combat ETS exposure in children.